Characterization of Turkish mulberry genetic resources based on antioxidant capacity, biochemical composition, nutrient content, and morphological traits of leaves - Yazgan Tunç; Ali Khadivi; Mehmet Yaman; Kadir Uğurtan Yılmaz; Ercan Yıldız; Adem Güneş; Yusuf Murat Keçe; Duygu Özelçi; Daya Shankar Mishra (Scientific Reports)
Abstract This study investigated the antioxidant capacity, biochemical composition, nutrient content, and morphological traits of 21 mulberry genotypes grown under the same ecological conditions in Türkiye. These genotypes, representing Morus alba, M. nigra, M. rubra, and unidentified species, were cultivated to evaluate their genetic diversity and potential for functional applications. The genotype ‘Gosho Erami’ exhibited the highest performance across total antioxidant activity (87%), phenolic contents (40.58 mg GAE/100 g), and flavonoid contents (6.48 mg QE/100 g), while ‘Hatay Dörtyol Mordut’ had the lowest values (50.61%, 20.33 mg GAE/100 g, and 2.11 mg QE/100 g, respectively). Among nutrients, calcium content ranged from 5733 (‘Şelale Karadut’) to 32.525 mg/kg (‘44 MRK 01’), iron content changed between 59.45 (‘Mersin Köy Hizmetleri Mordut’) and 101.99 mg/kg (‘Topu Beyaz-2 (24-03)’), and zinc content varied between 7.50 (‘Kastamonu Beyaz’) and 16.37 mg/kg (‘Topu Beyaz-2 (24 − 03)’). Leaf morphology showed significant variation, with leaf length ranging from 65.4 (‘Amasya Beyaz’) to 135.3 mm (‘44 BA 05’) and petiole length from 13.38 (‘Erzincan Karadut’) to 46.36 mm (‘44 BA 05’). Principal component analysis revealed that the first three components accounted for 56.05% of the total variation, with PC1 (26.85%) being primarily influenced by potassium (0.35), sodium (0.32), manganese (0.30), zinc (0.30), aluminum (0.26), and leaf length (0.26). Multiple regression analysis showed that manganese significantly influenced total phenolics (β = 0.38, p < 0.03) and total flavonoids (β = 0.75, p < 0.00). Heat map analysis clustered the genotypes ‘Gosho Erami’ and ‘44 BA 05’ with total phenolics, flavonoids, and antioxidant capacity, highlighting their biochemical superiority. This study has shown that different origin mulberry genotypes grown in Türkiye exhibit significant genetic diversity and have important potential for nutritional supplements and functional food applications. Our study’s 21 quantitative data sets revealed that the genotypes with the highest overall values were ‘25 UZ 08’, ‘Ichinose’, and ‘44 BA 05’, while those with the lowest values were ‘44 MRK 01’, ‘Ship Yeoung’, and ‘Şelale Karadut’. These findings emphasize the importance of integrating biochemical, nutritional, and morphological analyses to maximize the agricultural and economic benefits of mulberry resources.